Success rate of three capping materials used in pulpotomy of primary molars: A randomized clinical trial - Randa Youssef Abd Al Gawad; Rasha Mohamed Hatem Hanafy (Elsevier, 2021)
Background: Carious primary molars, symptomless, or with reversible pulpitis are most frequently treated with pulpotomy to maintain arch integrity, otherwise they would be extracted. The present study was conducted to assess clinically and radiographically the success rate of three capping materials: Nanohydroxyapatite (NHA), Mineral Trioxide Aggregate (MTA), and Formocresol (FC) in pulpotomy of primary molars. Methods: A clinical trial was carried out on healthy, four to eight years old children, with 72- second primary molars indicated for pulpotomy. Molars were divided into 3 equal groups (24 teeth each) designated to NHA (group 1), MTA (group 2), and FC (group 3) as pulp medicaments. Treated teeth were finally restored with stainless steel crowns. Subjects were monitored clinically and radiographically after three, six, and twelve months. Statistical analysis was presented as intended to treat analysis. Categorical data were analyzed using Fisher's exact test. The significance level was set at p ≤ 0.05. Statistical analysis was performed using SPSS, version 26. Results: By the end of the twelve months, the number and percentages of successfully treated molars for Group (1), Group (2) and Group (3) were 10 (41.7%), 19 (79.2%) and 18 (75.0%) respectively; with (NHA) group showing a significantly lower rate of success, (p = 0.019). Conclusions: MTA is still the material of choice for pulpotomy in primary molars. Trial Registration: This trial was registered on Clincal.Trial.gov (https://clinicaltrials.gov), on February 8, 2019 (Retrospectively registered). The protocol ID is 181053. The Identifier is NCT03833557.